Melatonin Alleviates Hypoxia-Induced Apoptosis of Granulosa Cells by Reducing ROS and Activating MTNR1B-PKA-Caspase8/9 Pathway - Jing-Li Tao; Xuan Zhang; Jia-Qi Zhou; Cheng-Yu Li; Ming-Hui Yang; Zhao-Jun Liu; Liang-Liang Zhang; Shou-Long Deng; Lu Zhang; Ming Shen; Guo-Shi Liu; Hong-Lin Liu (MDPI AG, 2021)
In mammalian ovaries, the avascular environment within follicular cavity is supposed to cause hypoxic status in granulosa cells (GCs), leading to apoptotic cell death accompanied by cumulative reactive oxygen species (ROS) production. Melatonin (N-acetyl-5-methoxytryptamine, MT), a broad-spectrum antioxidant that exists in porcine follicle fluid, was suggested to maintain GCs survival under stress conditions. In this study, using the established hypoxic model (1% O2) of cultured porcine GCs, we explored the effect of MT on GCs apoptosis. The results showed that MT restored cell viability and reduced the apoptosis of GCs during hypoxia exposure. In addition, GCs treated with MT exhibited decreased ROS levels and increased expression of antioxidant enzymes including heme oxygenase-1 (HO-1), glutathione S-transferase (GST), superoxide dismutase 1 (SOD1), and catalase (CAT) upon hypoxia incubation. Moreover, the hypoxia-induced expression of cleaved caspase 3, 8, and 9 was significantly inhibited after MT treatment. In contrast, blocking melatonin receptor 2 (MTNR1B) with a competitive antagonist 4-phenyl-2-propionamidotetralin (4P-PDOT) diminished the inhibitory effects of MT on caspase 3 activation. By detecting levels of protein kinase (PKA), a downstream kinase of MTNR1B, we further confirmed the involvement of MT-MTNR1B signaling in mediating GCs protection during hypoxia stress. Together, the present data provide mechanistic evidence suggesting the role of MT in defending GCs from hypoxia-induced apoptosis.